REVIEW: STUDENTS’ ENGAGEMENT IN BLENDED LEARNING - Nugroho, Nugroho (Jurnal Muara Pendidikan, 2025)
One of the success factors in blended learning is student involvement. As a result, the use of technology to influence student engagement and the efficacy of learning experiences is worth investigating. This research aims to find out what type of student involvement is in the blended learning model. Student involvement includes three aspects, namely behavioral, cognitive, and emotional aspects. There are many learning management systems used to carry out blended learning, including schoology, canvas, quipper, and others. This research uses a literature review method. Data was collected from the Scopus database. Data filtering with inquest and inclusion criteria. The findings; In various investigations on behavioral, emotional, and cognitive participation, not all of the data indicated that student involvement in blended learning increased. Other publications may not identify certain categories of engagement, yet evidence indicates improved engagement in blended learning. One article discovered behavioral, cognitive, and affective engagement. This study also demonstrates improved student participation in blended learning. This research can be continued by expanding the database and period.